1998
DOI: 10.1002/masy.19981260122
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of adhesive bonding of thermoplastic polymers by different surface treatments

Abstract: Injection moulded samples of six species of thermoplastic polymers were exposed to different surface treatments and successively glued together to form single lap shear joints. Lap shear strength and failure mode of these specimens were examined. The surfaces obtained after treatment were characterized by electron spectroscopy for chemical analysis, contact angle measurements and atomic force microscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…This indicates that the improvement of adhesion properties using plasma or UV is caused by different mechanisms. In [20] contact angles post-treatment were found to increase. This contradicts the results detailed in [21] and [22].…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…This indicates that the improvement of adhesion properties using plasma or UV is caused by different mechanisms. In [20] contact angles post-treatment were found to increase. This contradicts the results detailed in [21] and [22].…”
Section: Introductionmentioning
confidence: 88%
“…An important consideration for the viability of a surface treatment in industry is the treatment stability. In [20] it was found that the lap shear strength of UV treated semi-crystalline samples of polymers remained relatively consistent for up to 30 days. This is an advantage of UV treatment with respect to plasma treatment as, currently, a material treated with plasma has to be bonded almost immediately, meaning that surface treatment and adhesive bonding must occur in two very close facilities.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations